Droplet microfluidic screening to engineer angiotensin-converting enzyme 2 (ACE2) catalytic activity - Evelyn F Okal; Philip A. Romero; Pete Heinzelman (Journal of Biological Engineering)
Abstract Background Angiotensin-Converting Enzyme 2 (ACE2) is a crucial peptidase in human peptide hormone signaling, catalyzing the conversion of Angiotensin-II to Angiotensin-(1–7), which activates the Mas receptor and elicits vasodilation, increased blood flow, reduced inflammation, and decreased pathological tissue remodeling. This study leverages protein engineering to enhance ACE2’s therapeutic potential for treating conditions such as respiratory viral infections, acute respiratory distress syndrome, and diabetes. Surrogate substrates used in traditional high-throughput screening methods for peptidases often fail to accurately mimic native substrates, leading to less effective enzyme variants. Here, we developed an ultra-high-throughput droplet microfluidic platform to screen peptidases on native peptide substrates. Our assay detects substrate cleavage via free amino acid release, providing a precise measurement of biologically relevant peptidase activity. Results Using this new platform, we screened a large library of ACE2 variants, identifying position 187 as a hotspot for enhancing enzyme activity. Further focused screening revealed the K187T variant, which exhibited a fourfold increase in catalytic efficiency (k cat /K M ) over wild-type ACE2. Conclusions This work demonstrates the potential of droplet microfluidics for therapeutic peptidase engineering, offering a robust and accessible method to optimize enzyme properties for clinical applications.